Analisis Kesiapan Pelaksanaan Rekam Medis Elektronik (RME) Dengan Metode Doctor's Office Quality-Information Technology (DOQ-IT) di Klinik Pratama Polkesmar - Meilinda Asrining Hapsari; Kismi Mubarokah (Politeknik Negeri Jember, 2023)
In order to realize digital transformation, quality data integration is an important element, especially in the field of health services. All Health Service Facilities are expected to have implemented Electronic Medical Records (EMR) following the provisions no later than December 31, 2023. In order to comply with these regulations, health service facilities must prepare all the components needed to implement EMR. The purpose of this study was to analyze the readiness of implementing RME using the Doctor's Office Quality-Information Technology (DOQ-IT) method at the Polkesmar Primary Clinic. The type of research used was descriptive quantitative. Methods of data collection were through filling out questionnaires. Ease of use analysis was done using the EHR Assessment and Readiness Starter Assessment from DOQ-IT. The total readiness score of the Polkesmar Primary Clinic in implementing EMR was 128,45 in category III, which meant that the Polkesmar Primary Clinic was very ready to implement EMR. Readiness for implementing EMR could be ranked as the strongest, namely Human Resources readiness (4,50), Governance and Leadership readiness (4,64), Organizational Work Culture readiness (4,69), and IT Infrastructure readiness (4,54).